(3JjLGf GdYfhGf Ydi eKGd YfhGf GdTQas - (3CMeO Hf YHO GdQGRb GdeZQHjs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg Ydi cd MGd Yde GdJUha CMeO ef djS dg ef EHJOG SHMGfg hdG ENJJGe CHOkG hHYO gPi fHPI GdJUha aGddg QH GdYGQT MJekG aGYQa s
(3BNQgG (B:s
(3ddfhQ gPG GdegJOi Je GdcJGH YfhGf GdTQa hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJUha hGdBOGH GdTQYjIs